Micro-Simulation of Social Security Reforms in Belgium - Raphaël Desmet; Alain Jousten; Sergio Perelman; Pierre Pestieau (Institute for the Study of Labor (IZA), 2003)
The present paper analyzes the budgetary impact of various Social Security reforms in the Belgian institutional setting. Our approach relies on parameters that were derived in Dellis et alii (2002) using a micro-modeling strategy. Focusing our attention on a hypothetical age cohort, we illustrate the budgetary impact that the reforms considered might have on the budget of the federal government.
Keywords: H3; J0; I3; 330; aging; retirement; incentives; pension reform; Rentenreform; Alterssicherung; Wirtschaftspolitische Wirkungsanalyse; Simulation; Altersgrenze; Öffentlicher Haushalt; Belgien; Mikrosimulation